2017
DOI: 10.3892/or.2017.6113
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide inhibits the metastasis of type Ⅱ esophageal‑gastric junction adenocarcinoma cells via NF-κB and PI3K/AKT signaling pathways in vitro

Abstract: Esophageal-gastric junction adenocarcinoma (AEG) is an aggressive tumor with high incidence and dismal prognosis worldwide. Despite significant advances in therapeutic strategies, the 5-year survival rate still remains low. Diallyl disulfide (DADS), which is one of the major volatile components isolated from garlic, has been shown to have multi-targeted antitumor activities in a variety of cancer cells. However, the exact anti-metastatic effects and underlying molecular mechanisms of DADS in AEG have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…ECM degradation is positively mediated by MMP/TIMP expression, as alterations in the balance of MMP/TIMP expression lead to the invasion and migration of OC cells [19,20]. Here, we observed that PRR11 silencing mitigated the invasion and migration of siRNA-PRR11 HO-8910 cells, which was associated with reduced levels of MMP2, but increased levels of TIMP-2 in OC.…”
Section: Discussionmentioning
confidence: 61%
“…ECM degradation is positively mediated by MMP/TIMP expression, as alterations in the balance of MMP/TIMP expression lead to the invasion and migration of OC cells [19,20]. Here, we observed that PRR11 silencing mitigated the invasion and migration of siRNA-PRR11 HO-8910 cells, which was associated with reduced levels of MMP2, but increased levels of TIMP-2 in OC.…”
Section: Discussionmentioning
confidence: 61%
“…These results suggest that under acidic conditions (pH 3.0), ‘Ershuizao’ and ‘Hongqixing’ garlic easily react and convert sucrose to 5-hydroxymethylfurfural, which has antitumor effects. However, previous studies on the antitumor effects of garlic focused on other organosulphur compounds, such as diallyl disulphide (DADS) (Liao et al, 2009; Yin et al, 2018), DATS (Li & Lu, 2002), and ajoene (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that under acidic conditions (pH 3.0), 'Ershuizao' and 'Hongqixing' garlic easily react and convert sucrose to 5-Hydroxymethylfurfural, which has antitumor effects. However, previous studies on the antitumor effects of garlic focused on other organosulfur compounds, such as diallyl disulfide (DADS) (Liao et al 2009;Yin et al 2018), DATS (Li & Lu 2002), and ajoene .…”
Section: Discussionmentioning
confidence: 99%